Shariah and accounting principles for calculating the actual cost of lending services among Islamic banks: case of Malaysia - Saleh, Abdulmajid Obaid Hasan; F. Al-Shaghdari, F. Al-Shaghdari; T. Ali Hakami, T. Ali Hakami (Springer Science and Business Media Deutschland GmbH, 2022)
Shariah associations and bodies have permitted Islamic Banks to take the actual cost of lending, that’s was due to the permissibility of differentiating between the loan and the services accompanying its amortization, restriction and follow-up, as these proceedings are not included in the principal of the loan. The Islamic banks differed in applying the concept of actual cost based on a lump sum and a percentage. The academies also differed in the methods of taking this cost, because the fee-based services provided by Islamic banks may bring some legitimate issues related to the imposition of fees or the actual cost. The research adopted the descriptive and analytical approach and the quantitative method by studying the case of Malaysian Islamic banks in accordance to the accounting principles and the related rules. The research concluded that the total cost should be calculated by the application of the following equation: Total cost (TC) = Penalty (P) + Compensation (C). In addition, the total cost imposed for late payment must meet the following two conditions: First, the total cost should not exceed the cost that the client bears in the traditional bank, with the condition that the total cost of the penalty is not doubled on the late installments or the due principal amount. Secondly, after calculating the total cost imposed on the client for the late payment, the Islamic bank must submits a written request to the Central Bank, explaining the justifications for imposing late payment fees, the circumstances that led to the imposition of late payment fees, and attaching working a plan after its approval by the Shariah Committee of the Islamic bank.